Penerapan Zero Waste dengan Teknik Fabric Manipulating Tucking pada Ready to Wear - Astuti Jamilatul Nimah; Arina Haq; Edi Swasana (Akademi Kesejahteraan Sosial Ibu Kartini Semarang, 2026)
The fashion industry produces large amounts of textile waste, necessitating sustainable design solutions such as zero-waste fashion design. This study examines the application of zero-waste fashion using the fabric manipulation tucking technique to ready-to-wear clothing. The objective of this study is to determine how the tucking technique can be applied to zero-waste pattern design to produce efficient and aesthetically pleasing clothing. The research method used is Research and Development (R&D) with the ADDIE development model.The research results include five stages: In the analysis stage, the author examines the concepts of zero waste, the tucking technique, and ready-to-wear clothing. In the design phase, two zero-waste pattern concepts with variations of tucking were created as trials. Development was carried out through design validation and revisions based on expert input. Implementation was carried out with product production based on the refined final design. Finally, evaluation was carried out through product validation and final revisions until the product was finished. The results show that zero-waste design using the tucking technique can be implemented systematically, reducing waste and enhancing product uniqueness.Recommendations in this study highlight the importance of tucking stitch direction, accurate placement of zero-waste patterns, and the use of excess fabric as an additional tucking accent to reduce looseness and optimize fabric usage. Selection of appropriate fabrics to support the aesthetic results and effectiveness of the Tucking technique in ready-to-wear fashion products.